Two program comprehension tools for automatic parallelization - Di Martino, B.; Kessler, C.W. (IEEE concurrency, 2000)
The authors compare two program-comprehension systems targeted to support automatic parallelization: PARAMAT (PARAllelization by pattern MATching) and the PAP (Parallelizable Algorithmic Patterns) Recognizer. The authors illuminate the main differences of each method, discussing the tradeoff between the speed of the first and the generality of the second.